A Role for Vasoactive Intestinal Peptide Interneurons in Neurodevelopmental Disorders - Goff, Kevin M; Goldberg, Ethan M (Developmental neuroscience, 2021)
GABAergic inhibitory interneurons of the cerebral cortex expressing vasoactive intestinal peptide (VIP-INs) are rapidly emerging as important regulators of network dynamics and normal circuit development. Several recent studies have also identified VIP-IN dysfunction in models of genetically determined neurodevelopmental disorders (NDDs). In this article, we review the known circuit functions of VIP-INs and how they may relate to accumulating evidence implicating VIP-INs in the mechanisms of prominent NDDs. We highlight recurring VIP-IN-mediated circuit motifs that are shared across cerebral cortical areas and how VIP-IN activity can shape sensory input, development, and behavior. Ultimately, we extract a set of themes that inform our understanding of how VIP-INs influence pathogenesis of NDDs. Using publicly available single-cell RNA sequencing data from the Allen Institute, we also identify several underexplored disease-associated genes that are highly expressed in VIP-INs. We survey these genes and their shared related disease phenotypes that may broadly implicate VIP-INs in autism spectrum disorder and intellectual disability rather than epileptic encephalopathy. Finally, we conclude with a discussion of the relevance of cell type-specific investigations and therapeutics in the age of genomic diagnosis and targeted therapeutics.